Remote Patient Monitoring for Managing Interstitial Lung DiseaseTake-Home Points - Genevieve Gillett, MD; Rupal J. Shah, MD; Alison M. DeDent, MD; Erica Farrand, MD (CHEST Pulmonary)
Background: Hybrid health care delivery uses a combination of in-person and telehealth visits to deliver interstitial lung disease (ILD) care efficiently and flexibly. However, assessments of ILD activity and progression can be limited during telehealth visits. Remote patient monitoring (RPM) is an effective approach to evaluating ILD trajectories. However, in the United States, there has been limited uptake of RPM into ILD care models. Research Question: Can we define patient-level facilitators and barriers to implementing RPM into routine ILD care? Study Design and Methods: RPM data from spirometers and pulse oximeters were collected weekly from participants with newly diagnosed ILD. Additional data were collected using surveys and qualitative interviews in a parallel convergent mixed-methods design, reflexively analyzed for themes, and integrated using a triangulation protocol. Results: Sixty participants had a median age of 74 years; most were male (59%), White (60.7%), and diagnosed with idiopathic pulmonary fibrosis (50%). Adherence to weekly device use was high (90%) and participants thought RPM was an important (90%) and sustainable (87%) part of ILD care. Key barriers to RPM use included difficulty with spirometry technique, communication of results, and result interpretation. Interpretation: Our results indicate that RPM is a feasible, valuable, and sustainable component of routine ILD care. Applying an implementation science framework, patient-level barriers would be best addressed through (1) supervised device setup, (2) more efficient and frequent communication, and (3) improved patient education. Addressing these barriers may facilitate more widespread and successful implementation of RPM, with the potential to greatly improve patient engagement in ILD care.